The complete textbook of phlebotomy - Hoeltke, Lynn B. (Clifton Park, NY : Delmar, Cengage Learning, 2013)
With a strong emphasis on hands-on learning, this text helps students develop the phlebotomy related knowledge and skills they need to become confident, competent health care professionals. The text provides detailed content reflective of the latest practice standards and competencies of the phlebotomy profession in a way that connects it to actual practice. Step-by-step guidelines for more than 20 collection procedures are provided along with real-life scenarios and prompts that emphasize the phlebotomist?s legal and ethical role in decisions related to patient care. Full color photographs highlight important steps in each procedure along with proper equipment, while illustrations depict the components of anatomy critical to proper phlebotomy technique.